2008
DOI: 10.1111/j.1540-8159.2008.01152.x
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation Is Associated with Decreased Cardiac Sympathetic Response to Isometric Exercise in CHF in Comparison to Sinus Rhythm

Abstract: In this study, we demonstrate for the first time that the combination of AF and CHF is accompanied by a marked attenuation of the cardiac sympathetic response to acute hemodynamic stress. This implies AF is associated with a further impairment of baroreceptor response in CHF compared to SR. These findings present possible insights to the associated increased mortality and pathogenesis of AF with CHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
1
4
0
1
Order By: Relevance
“…Another study showed baroreflex sensitivity indices were significantly lower in the HUTT-positive group than in the HUTT-negative group, 8) and a blunted baroreflex associated with AF was demonstrated in patients with chronic heart failure as compared to patients with sinus rhythm. 30) In our study, in addition to a positive HUTT, we also found that increased left atrial diameter, duration of AF history, and sleep apnea were independent predictors of AF recurrence. These data were in line with previous findings.…”
Section: Discussionsupporting
confidence: 71%
“…Another study showed baroreflex sensitivity indices were significantly lower in the HUTT-positive group than in the HUTT-negative group, 8) and a blunted baroreflex associated with AF was demonstrated in patients with chronic heart failure as compared to patients with sinus rhythm. 30) In our study, in addition to a positive HUTT, we also found that increased left atrial diameter, duration of AF history, and sleep apnea were independent predictors of AF recurrence. These data were in line with previous findings.…”
Section: Discussionsupporting
confidence: 71%
“…Our findings are coherent with several previous studies reporting an association between altered autonomic nervous system functions and development of AF. Stimulation of the parasympathetic ganglia have been shown to play a critical role in triggering AF episodes 36,37 and heart failure patients with AF exhibit an altered sympathetic response to exercise compared with heart failure patients in sinus rhythm 38 . These alterations in the autonomic nervous system functions seem to precede the development of AF, perhaps explaining the predictive power of these measures.…”
Section: Discussionmentioning
confidence: 99%
“…Studies looking at the effects of exercise training on individuals with AF report an increased exercise capacity through 6MWT distance and significantly decreased resting HR [176][177][178] .…”
Section: Appendix J: Extra Considerations For Individuals With Atrialmentioning
confidence: 99%